What Every Educator Should Teach to Their Learners to Confront the 21st Century Life and Career? - Mas Muhammad Idris (Mozaic : Islam Nusantara, 2025)
In the context of 21st-century education development, educators are increasingly designing instructional methods aimed at equipping students with essential competencies to meet the unique demands of this era. Core skills such as expert thinking, effective communication, exploratory collaboration, and creative learning activities are fundamental for navigating the complexities of modern life and the global workforce. However, these competencies alone are insufficient for future readiness. This article argues that deeper cognitive and socio-cultural stimulation is necessary for students’ success in the 21st century. Drawing from relevant literature, this study proposes that educators should emphasize three interrelated capabilities: strengthening philosophical literacy as a foundational skill; enhancing the ability to comprehend and respond to social environments; and cultivating cross-cultural understanding. Furthermore, this article recommends a structured pedagogical approach that includes brainstorming activities, fostering life wisdom, and promoting intercultural information exchange among students. These strategies are expected to better prepare learners for global educational and professional challenges in the 21st century.